Isolation and Potential Testing of North Sumatera Berastagi Agricultural Soil In Degrading Marshal Insecticide With Carbosulfan Active Material - Nunuk Priyani (International Journal of Ecophysiology, 2020)
The isolation of bacteria from Berastagi agricultural soil North Sumatera has been done. The aim is to evaluate their ability in degrading carbosulfan. Sixteen bacterial isolates were obtained using selective media Bushnel Hass Agar (BHA) containing 12 ppm of carbosulfan. The parameters observed were the growth of isolates, biosurfactant activity, biosurfactant concentration, and the residue of carbosulfan after 21 days of incubation. The result showed that all isolates were able to degrade carbosulfan as the sole carbon source. Two isolates namely JBM 3 (isolate from citrus agricultural soil Berastagi) and KBM 1 (isolate from cabbage agricultural soil Berastagi) were selected for further test to determine their ability to degrade carbosulfan. The results showed that both of the isolates were able to degrade carbosulfan. Compare to control, isolate JBM 3 was able to decrease the concentration of carbosulfan by 33.33%, while isolate KBM 1 was able to reduce carbosulfan concentration up to 40.47%.